(untitled) (Medical Forum Monthly, 2022)
Objective: To calculate and estimate the 3rd ventricular measurements in different age groups including both genders. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Anatomy with the collaboration of Radiology Department J.P.M.C Karachi from November 2019 to December 2020. Materials and Methods: Patients with any gross pathology of brain was excluded whereas MRI with no clinical manifestation of 206 patients were included. 3rd ventricle was measured for its dimensions on MRI via Tesla 1 weighted (T1-weighted), Tesla 2 weighted (T2-weighted) and Fluid Attenuated Inversion Recovery (FLAIR) on coronal, sagittal and transverse plane on different levels by 3D technique. Dimensions of 3rd ventricles were measured by measuring the length, width and height of third ventricle. Results: Out of the 206 participants 106 (51.5%) were in group A and 100 (48.5%) were in group B. In total, males were 102 (49.5%) and 104 (50.5%) were females. Mean age of group A was 29.3 ± 6.88 while group B mean age was 51.7 ± 6.58. The result showed that length of 3rd ventricle was found greater in females as compared to males while width and height found greater in male than females. However in comparison with age third ventricle height was found to be decreased in size while width and length was increased with advancement of age. Conclusion: Study showed that variations are found in measurements of 3rd ventricle in different subjects with age and gender and when we compared it with the studies in different areas and population. This will be helpful for surgeons, neuro-physcians and radiologists to investigate, manage and treat a disease of brain.